application of the linear interaction energy method (LIE) to estimate the binding free energy values of escherichia coli wild-type and mutant arginine repressor c-terminal domain (ARGRC)-l-arginine and argrc-l-citrulline protein-ligand complexes - Asi, A.M.; Rahman, N.A.; Merican, Amir Feisal (Elsevier, 2004)
Protein-ligand binding free energy values of wild-type and mutant C-terminal domain of Escherichia coli arginine repressor (ArgRc) protein systems bound to L-arginine or L-citrulline molecules were calculated using the linear interaction energy (LIE) method by molecular dynamics (MD) simulation. The binding behaviour predicted by the dissociation constant (K-d) calculations from the binding free energy values showed preferences for binding Of L-arginine to the wild-type ArgRc but not to the mutant ArgRc(D128N). On the other hand, L-citrulline do not favour binding to wild-type ArgRc but prefer binding to mutant ArgRc(D128N). The dissociation constant for the wild-type ArgRc-L-arginine complex obtained in this study is in agreement with reported experimental results [J. Mol. Biol. 235 (1994) 221-230]. Our results also support the experimental data for the binding Of L-citrulline to the mutant ArgRc(D128N) [J. Mol. Biol. 279 (1998) 753-760]. These showed that LIE method for protein-ligand binding free energy calculation could be applied to the wild-type and the mutant E. coli ArgRc-L-arginine and ArgRc-L-citrulline protein-ligand complexes and possibly to other transcriptional repressor-co-repressor systems as well. (C) 2003 Elsevier Inc. All rights reserved.